“Oh, We Don’t Want the Men Around.” The Experience of Men in Nursing During Prelicensure Labor and Delivery Clinical Rotation - Kechi Iheduru-Anderson; Chimezie J. Agomoh (Nursing Research and Practice)
Conclusion: This study explored the experiences of male nursing students during their clinical rotations in the labor and delivery unit. The findings will add to the body of knowledge on gender and nursing education and provide valuable insight into the experiences of male nursing students, which can be used to support and improve nursing education in this area.